2009
DOI: 10.15288/jsad.2009.70.583
|View full text |Cite
|
Sign up to set email alerts
|

Automatic Alcohol Associations: Gender Differences and the Malleability of Alcohol Associations Following Exposure to a Dating Scenario

Abstract: ABSTRACT. Objective: Little research has examined contextual infl uences on implicit measures of alcohol-related cognitions. The current study investigated whether contexts involving alcohol or social dating would affect automatic alcohol approach-avoid associations. Method: Undergraduates (n = 112 women, 109 men) completed an Implicit Association Test (IAT) that measured alcohol approach-avoid associations before and after reading a vignette about a date that differed on two dimensions: (1) whether alcohol wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
17
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 49 publications
2
17
1
Order By: Relevance
“…Another potential explanation for these findings is related to how automatic processes form, which is through experience and the environment (e.g., Lindgren, Neighbors, Ostafin, Mullins, & George, 2009). We proposed that individuals with experience with or exposure to alcohol may develop automatic alcohol-related associations such that they may be more likely to turn to alcohol during times of self-awareness induced discomfort.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Another potential explanation for these findings is related to how automatic processes form, which is through experience and the environment (e.g., Lindgren, Neighbors, Ostafin, Mullins, & George, 2009). We proposed that individuals with experience with or exposure to alcohol may develop automatic alcohol-related associations such that they may be more likely to turn to alcohol during times of self-awareness induced discomfort.…”
Section: Discussionmentioning
confidence: 99%
“…The IAT was used to examine automatic associations with alcohol using pictures and words as stimuli (Lindgren et al, 2009; Ostafin & Palfai, 2006) and was presented using Inquisit software (Draine, 2004). The seven phases of the IAT include practice tasks to orient subjects with the sorting rules and stimulus materials (Nosek, Greenwald, & Banaji, 2007).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, implicit measures may be more sensitive to changes in mood or environmental cues. For example, several studies have found changes in activation of alcoholrelated cognitions following experimental mood manipulation (Birch et al, 2004;Krank et al, 2005), in response to alcohol-related cues (Rather and Goldman, 1994;Stritzke et al, 2004), and after exposure to vignettes depicting unsuccessful social situations (Lindgren et al, 2009). Van den Wildenberg et al (2006) also found that implicit arousal associations were related to heart rate following alcohol consumption, such that higher implicit arousal associations were related to a decrease in heart rate.…”
Section: Implicit and Explicit Cognitions About Alcoholmentioning
confidence: 99%
“…It was found that in alcohol related contexts, such as a bar laboratory (Lau-Barraco & Dunn, 2009) or reading a vignette about a date where alcohol is present (Lindgren, Neighbors, Ostafin, Mullins & George, 2009), IAC tended to increase. However, Coronges, Stacy & Valente (2011) study concluded that in a group of high school friends, social influence had a greater impact on implicit associations than on behavior.…”
Section: Topic 6: Context Influence On Iacmentioning
confidence: 99%